Efektivitas Sistem Computer Assisted Test (CAT) dalam Meningkatkan Transparansi dan Objektivitas Seleksi Calon Pegawai Negeri Sipil (CPNS) - Hilma Harmen; Najwa Annisa Putri; Namira Shafalda Prabudi; Salsabila Mawaddah Damanik; Felicia Dinata Pane (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
The selection process for Civil Servant Candidates (CPNS) requires a fair, transparent, and objective system for assessing participant competency. Previous conventional selection methods still face various issues, such as a lack of transparency, lengthy administrative processes, and the potential for human bias in assessments. To improve the quality of selection, the government, through the National Civil Service Agency (BKN), has implemented the Computer Assisted Test (CAT) system as a technology-based selection method. This study aims to analyze the effectiveness of the CAT system in increasing transparency, objectivity, and efficiency of the CPNS selection process from a human resource management perspective. This study uses a qualitative descriptive approach through literature studies and analysis of various documents related to the implementation of the CAT. The study results indicate that the CAT system is able to increase transparency through the direct presentation of scores, increase objectivity through automated assessment by the system, and increase the efficiency of the selection process. The implementation of this system also requires strengthening the technological security system and increasing supervision in the selection process, such as controlling access to exam equipment, using more secure networks, and stricter supervision at the exam location to maintain the integrity and credibility of the CAT-based CPNS selection process.